Transcriptomic and functional analyses of the piRNA pathway in the Chagas disease vector Rhodnius prolixus. - Tarcisio Brito; Alison Julio; Mateus Berni; Lisiane de Castro Poncio; Emerson Soares Bernardes; Helena Araujo; Michael Sammeth; Attilio Pane (Public Library of Science (PLoS), 2018)
The piRNA pathway is a surveillance system that guarantees oogenesis and adult fertility in a range of animal species. The pathway is centered on PIWI clade Argonaute proteins and the associated small non-coding RNAs termed piRNAs. In this study, we set to investigate the evolutionary conservation of the piRNA pathway in the hemimetabolous insect Rhodnius prolixus. Our transcriptome profiling reveals that core components of the pathway are expressed during previtellogenic stages of oogenesis. Rhodnius' genome harbors four putative piwi orthologs. We show that Rp-piwi2, Rp-piwi3 and Rp-ago3, but not Rp-piwi1 transcripts are produced in the germline tissues and maternally deposited in the mature eggs. Consistent with a role in Rhodnius oogenesis, parental RNAi against the Rp-piwi2, Rp-piwi3 and Rp-ago3 results in severe egg laying and female adult fertility defects. Furthermore, we show that the reduction of the Rp-piwi2 levels by parental RNAi disrupts oogenesis by causing a dramatic loss of trophocytes, egg chamber degeneration and oogenesis arrest. Intriguingly, the putative Rp-Piwi2 protein features a polyglutamine tract at its N-terminal region, which is conserved in PIWI proteins encoded in the genome of other Triatomine species. Together with R. prolixus, these hematophagous insects are primary vectors of the Chagas disease. Thus, our data shed more light on the evolution of the piRNA pathway and provide a framework for the development of new control strategies for Chagas disease insect vectors.